Successful Curriculum Change in Health Management and Leadership Studies for the Specialist Training Programs in Medicine in Finland - Parviainen, Heli M.; Halava, Heli; Leinonen, Esa V. J.; Kosunen, Elise; Rannisto, Pasi-Heikki (Frontiers in Public Health, 2018)
In Finland, the specialization programs in Medicine and Dentistry can be undertaken at all five university medical faculties in 50 specialization programs and in five programs for Dentistry. The specialist training requires five or six years (300-360 ECTS credits) of medical practice including nine months of service in primary health care centers, theoretical substance specific education, management studies, and passing a national written exam. The renovation of the national curriculum for the specialization programs was implemented, first in 2008 and officially in August 2009, when theoretical multi-professional social, health management and leadership studies (10-30 ECTS credits) were added to the curriculum. According to European Credit Transfer and Accumulation System (ECTS), 1 ECTS credit (henceforth, simply “ECTS”) means 27-30 hours of academic work . National guidelines for the multi-professional leadership training include the basics of organizational management and leadership, the social and healthcare system, human resources (HR) management, leadership interaction and organizational communication, healthcare economy, legislation (HR) and data management. Each medical faculty has implemented management studies autonomously but according to national guidelines. This paper will describe how the compulsory management studies (10 ECTS) have been executed at the Universities of Tampere and Turku. In Tampere, the 10 ECTS management studies follow a flexible design of six academic modules. Versatile modern teaching methods such as technology-assisted and student orientated learning are used. Advanced supplementary management studies (20 ECTS) are also available. In Turku, the 10 ECTS studies consist of academic lectures, portfolio and project work. Attendees select contact studies (4-6 ECTS) from yearly available 20 ECTS and proceed at their own pace. Portfolio and project comprise 2-5 ECTS each. The renovation of medical specializing physicians’ management and leadership education has been a successful reform. It has been observed that positive attitudes and interest towards management overall are increasing among younger doctors. In addition, management and leadership education will presumably facilitate medical doctors’ work as managers also. Continuous development of medical doctors’ management and leadership education for physicians and dentists is needed while the changing and complex healthcare environment requires both professional and leadership expertise.